2019
DOI: 10.1002/polb.24817
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin for the strain rate dependence of mechanical response of fluoroelastomer F2314

Abstract: The structural evolution of fluoroelastomer F2314 is studied during uniaxial tensile in a large strain rate range (0.1–150 s−1) with the combination of a homemade high‐speed stretching device and in situ small‐ and wide‐angle X‐ray scattering techniques. Based on the mechanical behaviors and structural evolutions, three strain rate regions (I–III) are defined. The microphase‐separated structure plays an important role in the mechanical response of F2314. In Region I, deformation of soft domains is the main pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The relative bulk crystallinity (χ c ) can be calculated using the following equation: , where A c and A a represent the areas of the fitted crystalline and amorphous peaks, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The relative bulk crystallinity (χ c ) can be calculated using the following equation: , where A c and A a represent the areas of the fitted crystalline and amorphous peaks, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…After the integration, the 1D curves were deconvoluted by multipeak fitting by using the Gaussian method. The relative bulk crystallinity (χ c ) was calculated using the following eq : , χ c = prefix∑ A c / true( A normalc + A normala true) × 100 % …”
Section: Experimental Methodsmentioning
confidence: 99%
“…[24,25] The crystallization behavior of this kind of P(VDF-CTFE) has a significant effect on the mechanical strength and adhesion of their films. Chang et al [26] have proposed that the coexistence of crystalline and amorphous domains with different molecular chain mobility is the main reason for the strain rate dependence of mechanical response. Wang et al [27] have found that introducing the carbon-carbon double bond into the amorphous region can reduce the mobility of the polymer chain and improve the yield and breaking strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al. [ 26 ] have proposed that the coexistence of crystalline and amorphous domains with different molecular chain mobility is the main reason for the strain rate dependence of mechanical response. Wang et al.…”
Section: Introductionmentioning
confidence: 99%